Efforts to Increase Scientific Literacy and Thinking Process by Higher Order Thinking Skills - Setyasih, Astin Dwi; Hartono, Hartono; Prasetyo, Andreas Priyono Budi (Journal of Primary Education, 2019)
The research objective is to develop thematic teaching materials to improve scientific literacy skills and the thinking process of higher order thinking skills. This research uses the R & D (Research and Development) method with the design of Borg & Gall. The products resulted in this research is thematic teaching material oriented to scientific literacy and higher order thinking skills. Data analysis techniques used in this research include analysis of quantitative descriptive data related to validity and legibility of teaching materials. To determine the effectiveness of teaching material used normalized gain test. The results of this study indicate that the instructional material developed is valid and contains all the components of scientific literacy which include science as the body of knowledge, science as a way of investigating, science as a way of thinking, and the interaction between technology science and society in a balanced curriculum-oriented 2013. Learning by using the developed teaching material increase the students’ scientific literacy, namely the students’ ability to apply science to solve a problem. After learning with developed teaching material, the higher order thinking process is improved. Students’ thinking skills enable them to work on problems with operational analysis, evaluation, and creation work. Based on data analysis it can be concluded that the development thematic teaching material oriented to scientific literacy and higher order thinking skills is effective in improving scientific literacy and the thinking process of students of higher order thinking skills.